Produção e eficiência de biofertilizante e de bioprotetor com quitosana no pimentão - SANTANA, Rosângela Souza de (2012)
Green pepper is one of the most economic importance in the Brazilian market, and also is a horticultural crop very exigent in soil fertility, and it is known that in Brazil the soil in a general have low nutrient content, which increase the need for use of organic and mineral fertilizers. The production of fertilizers from natural phosphate (apatite) and potash rocks (biotites) represent a microbiological process that led to increase elements availability to provide nutrients for plant growth, and it is a practical and economic process. The aim of this study was to evaluate the PK rock biofertilizer mixed with earthworm compound inoculated with free living diazotrophic bacteria (BNPK) and of the bioprotect by introduction of fungi chitosan adding Cunninghamella elegans for use in organic agriculture. In a field experiment were evaluated the effects of the biofertilizer and the bioprotect (BNPK + C. elegans) on yield and nutrient uptake by green pepper (Capsicum annuum). The changes in some soil properties of a Red Yellow Latosol of the rainforest region of Pernambuco State, Brazil, were also observed. The experiment was carried out at the Horticultural Experimental Station of the Agronomic Institute of Pernambuco – IPA during the rain season period (March-August, 2011). The study was in a factorial (8x2), in split plot design, with eight fertilizer treatments and two sub treatments (with and without crustaceous chitosan applied on leaves), with four replicates. The fertilizer treatments were: (1) FNPK conventional mineral fertilizers applied in recommended rate (RR); (2) Biofertilizer - BNPK 50% RR; (3) BNPK 100% RR; (4) BNPK 150% RR; (5) PNPK (Bioprotect with fungi chitosan from C. elegans) 50% RR; (6) PNPK 100% RR; (7) PNPK 150% RR; (8) Control treatment (cow manure – 2.4 L plant-1). The best fruit yield was obtained with PNPK and BNPK, both applied in highest rate. There was significant difference among the fertilization treatments on the nutrients uptake. BNPK and PNPK reduced soil pH and increased total N available P and available K in soil, which probable will promote residual power. In the experiment was not observed incidence of soft rot diseases and it was not possible to compare the treatments. The results focus the great potential of PK rock biofertilizer with free living diazotrophic bacteria (BNPK) and bioprotect with fungi chitosan (BNPK + C. elegans) as alternative to NPK fertilization.